2016
DOI: 10.1007/s10899-016-9640-8
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence and Gambling: Exploring the Relationship Between Sense of Coherence, Gambling Behaviour and Gambling-Related Harm

Abstract: Understanding why some people experience problems with gambling whilst others are able to restrict gambling to recreational levels is still largely unexplained. One potential explanation is through salutogenesis, which is a health promotion approach of understanding factors which move people towards health rather than disease. An important aspect of salutogenesis is sense of coherence. Individuals with stronger sense of coherence perceive their environment as comprehensible, manageable and meaningful. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 100 publications
0
5
0
1
Order By: Relevance
“…Illegal gamblers are more likely to be at-risk, moderaterisk, or problem gamblers and less likely to be nonproblem gamblers than those who gamble legally. As a result, problem gambling is more common among people who gamble illegally online, resulting in issues such as depression, alcohol and drug abuse, family breakup, debt, and suicide [18][19][20][21].…”
Section: Issues With Illegal Gamblingmentioning
confidence: 99%
“…Illegal gamblers are more likely to be at-risk, moderaterisk, or problem gamblers and less likely to be nonproblem gamblers than those who gamble legally. As a result, problem gambling is more common among people who gamble illegally online, resulting in issues such as depression, alcohol and drug abuse, family breakup, debt, and suicide [18][19][20][21].…”
Section: Issues With Illegal Gamblingmentioning
confidence: 99%
“…Langham et al 94 found that an individuals' sense of coherence correlated strongly with gambling harms in all domains. Sense of coherence is the extent to which someone feels con dent in the predictability of his or her environment, and that things will generally turn out as expected.…”
Section: Sense Of Coherencementioning
confidence: 99%
“…Das Bereitstellen von E-Learning-Materialien oder "Helplines" für Hausärzte muss noch gewährleistet werden zur Unterstützung der eigenen Weiterbildung zu diesem Thema [50]. Stationäre Aufenthalte in therapeutischen Anstalten zählen zur Tertiärprävention und dienen als Rückfallprophylaxe mit transitorischem Unterbruch des Problemverhaltens [52].…”
Section: Regulationen Und Präventionunclassified